Esophageal Obstruction in Buffaloes (Bubalus bubalis) Resulting from the Ingestion of Potato Tubers - Shokry, Mohamed; Elkasapy, Abdelhaleem (Journal of Buffalo Science, 2021)
Total 32 emergency cases of buffaloes with esophageal obstruction resulting from the ingestion of potato tubers during their grazing are described. Treatment comprised immediate rumen trocarisation by a 14g syringe, premedication with IM xylazine (0.05 mg/kg), and passing a designed stout flexible tube to dislodge the obstruction to the rumen. The results were 100% successful recovery without any complications.